2019
DOI: 10.1101/832493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stathmin-2 Mediates Glucagon Secretion from Pancreatic α-Cells

Abstract: 21Inhibition of glucagon hypersecretion from pancreatic α-cells is an appealing strategy for the treatment of 22 diabetes. Our hypothesis is that proteins that associate with glucagon within alpha cell secretory granules 23 will regulate glucagon secretion, and may provide druggable targets for controlling abnormal glucagon 24 secretion in diabetes. Recently, we identified a dynamic glucagon interactome within the secretory granules 25 of the α cell line, αTC1-6, and showed that select proteins within the inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…In particular, treatment of α TC1-6 cells with insulin, which can override glucose-mediated regulation of glucagon secretion (Kawamori et al, 2009), appeared to recruit stathmin-2 (Stmn2 or SCG10) to the interactome, thus potentially identifying another inhibitor of glucagon secretion. In a subsequent study, we showed that Stmn2 is co-secreted in a regulated manner with glucagon, and when over-expressed, suppressed glucagon secretion by increasing its trafficking through the endolysosomal pathway in α TC1-6-cells (Asadi and Dhanvantari, 2020).…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In particular, treatment of α TC1-6 cells with insulin, which can override glucose-mediated regulation of glucagon secretion (Kawamori et al, 2009), appeared to recruit stathmin-2 (Stmn2 or SCG10) to the interactome, thus potentially identifying another inhibitor of glucagon secretion. In a subsequent study, we showed that Stmn2 is co-secreted in a regulated manner with glucagon, and when over-expressed, suppressed glucagon secretion by increasing its trafficking through the endolysosomal pathway in α TC1-6-cells (Asadi and Dhanvantari, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…NA plan-Apochromat oil differential interference contrast objective and NIS-Elements software (Nikon, Mississauga, Canada). Acquisition of high-resolution images was done by selecting Nyquist XY scan area, 1024×1024-pixel size scanning of the selected area and 2D-Deconvolution of the captured images, as we have done previously (Asadi and Dhanvantari, 2020).…”
Section: Preparation Of Pancreas Tissue Sections For Confocal Immunofluorescence Microscopymentioning
confidence: 99%
See 3 more Smart Citations